Transmission of multimedia content over wireless network - Lim, Calvin Yong Poo. (2010)
In this report, we will look at various wireless communication techniques which can be used to optimize multimedia streaming and transmission. The main focus will be on the optimization of transmission technique associated with multiple-input multiple-output (MIMO) transmission of multimedia content.